The Modified Rational Jacobi Elliptic Functions Method for Nonlinear Differential Difference Equations - Khaled A. Gepreel; Taher A. Nofal; Ali A. Al-Thobaiti (Journal of Applied Mathematics)
We modified the rational Jacobi elliptic functions method to construct some new exact solutions for nonlinear differential difference equations in mathematical physics via the lattice equation, the discrete nonlinear Schrodinger equation with a saturable nonlinearity, the discrete nonlinear Klein-Gordon equation, and the quintic discrete nonlinear Schrodinger equation. Some new types of the Jacobi elliptic solutions are obtained for some nonlinear differential difference equations in mathematical physics. The proposed method is more effective and powerful to obtain the exact solutions for nonlinear differential difference equations.